The Effect of Green Supply Chain Management on Organizational Environmental Performance (Starbucks Case Study in The City of Bandung) - Bangun Munthe (LPPM Universitas PGRI Sumatera Barat, 2024)
This study examines the influence of Green Supply Chain Management (GSCM) on organizational environmental performance in Starbucks coffee shops in Bandung City, Indonesia. The coffee shop industry has a high impact on the environment due to its use of plastic packaging. Starbucks, being one of the most popular coffee brands in Indonesia, has taken steps to implement